2022
DOI: 10.1029/2022gl099245
|View full text |Cite
|
Sign up to set email alerts
|

A Critical Role of the North Pacific Bomb Cyclones in the Onset of the 2021 Sudden Stratospheric Warming

Abstract: The role of North Pacific bomb cyclones in the onset of January 2021 sudden stratospheric warming (SSW) is examined by conducting a set of numerical model experiments. The control simulation, initialized 10 days before the SSW onset, successfully reproduces the SSW. As this event is preceded by the bomb cyclones in the North Pacific, their impact is tested by initializing the model without them. This sensitivity experiment shows much weaker polar‐vortex deceleration than the control simulation, resulting in no… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 8 publications
(9 citation statements)
references
References 37 publications
0
9
0
Order By: Relevance
“…This analysis therefore does not reveal any obvious discrepancies between model and observations in the ENSO‐Aleutian Low‐SSW relationship, but further work is needed to understand the observed La Niña teleconnection and more sensitive tests may yet reveal an error. Unpredictable variability in the Aleutian Low region (Cho et al, 2022), along with variability in other SSW precursor regions such as northern Eurasia (Lu et al, 2021; Rao et al, 2021), resulted in an increased likelihood of an SSW through tropospheric wave forcing. This appears to be unpredictable 1 month in advance with the current seasonal forecast system.…”
Section: Resultsmentioning
confidence: 99%
“…This analysis therefore does not reveal any obvious discrepancies between model and observations in the ENSO‐Aleutian Low‐SSW relationship, but further work is needed to understand the observed La Niña teleconnection and more sensitive tests may yet reveal an error. Unpredictable variability in the Aleutian Low region (Cho et al, 2022), along with variability in other SSW precursor regions such as northern Eurasia (Lu et al, 2021; Rao et al, 2021), resulted in an increased likelihood of an SSW through tropospheric wave forcing. This appears to be unpredictable 1 month in advance with the current seasonal forecast system.…”
Section: Resultsmentioning
confidence: 99%
“…It is found that the Ural blocking and Aleutian cyclones, which have been proposed as synoptic precursors of the 2021 SSW (Cho et al., 2022; Lu et al., 2021), do not have a significant impact on the SSW prediction in both models. Despite the small differences between ySSW and nSSW ensembles in the tropospheric precursors, the ySSW ensembles show much stronger wave fluxes at 100 hPa prior to the SSW onset than the nSSW ensembles.…”
Section: Summary and Discussionmentioning
confidence: 89%
“…In the weeks prior to the SSW onset, planetary‐scale eddy heat flux at 100 hPa, averaged over 45–75°N, sharply increased and its magnitude was maintained for longer than a week (red solid line). This strong upward flux of planetary‐scale waves was reported to be the major contributor to the 2021 SSW as it converged in the stratosphere and weakened the polar vortex (Cho et al., 2022; Lu et al., 2021). The zonal wavenumber one ( k = 1) and two ( k = 2) waves alternatively contributed to this strong eddy heat flux (green and blue dotted lines, respectively).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…SSWs are driven by the rapid amplification and breaking of upward propagating Rossby waves (Baldwin et al., 2021; Matsuno, 1971) associated with both tropospheric wave activity (Bao et al., 2017; Garfinkel et al., 2010; Martius et al., 2009; Matsuno, 1971) and internal stratospheric conditions (Christiansen, 1999; Holton & Mass, 1976; Matthewman & Esler, 2011; Scaife & James, 2000). There can be a high sensitivity to stratospheric conditions when the tropospheric flow is constrained (de la Cámara et al., 2017), as well as a critical role from wave generation by extratropical cyclones (Cho et al., 2022). Historical analysis suggest at least one third of SSWs immediately follow anomalous tropospheric wave activity, with the longer‐term accumulation of upward wave activity also important (Birner & Albers, 2017; de la Cámara et al., 2019; Polvani & Waugh, 2004).…”
Section: Introductionmentioning
confidence: 99%